PERHITUNGAN HARGA POKOK PRODUKSI (HPP) SEBAGAI DASAR PENENTUAN HARGA JUAL MIE DWR - Syafira Oky Tjatur Leonita; Endah Masrunik (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya, 2026)
This study examines how Cost of Goods Manufactured is calculated to determine the selling price at Mie DWR, a micro, small, and medium enterprise operating in the culinary sector. It addresses inaccurate production costs calculations that omit essential production components, causing undercosting and misleading pricing decisions. The research identifies, classifies, and measures all production cost elements using the full costing method, then compares results with the owner’s records and analyzes pricing implications. A descriptive qualitative case study was applied, collecting data through interviews, observations, and documentation, validated by source triangulation. Findings show a major gap between the owner’s COGM of IDR 4,196 per portion and the full costing result of IDR 15,250 per portion. Missing costs include labor, utilities, and equipment depreciation. The study concludes that incomplete records create hidden losses and inaccurate prices. Comprehensive costing supports better pricing, decisions, and sustainability for MSMEs in culinary businesses overall across competitive markets.